Store Atmosphere, Word of Mouth, dan Price Perception terhadap Keputusan Pembelian - Annatiqa Rismayanti; Ignatius Hari Santoso (IPM2KPE, 2023)
This study aims to describe the predictors of store atmosphere, word of mouth and price perception on purchasing decisions. This research method is descriptive quantitative. This study used 100 respondents with a purposive sampling technique. This study used the Smart LS version 4 program. The results showed that store atmosphere, word of mouth, and price perception were significant predictors of consumer purchasing decisions. In conclusion, the better the store atmosphere provided, the better the positive word of mouth given, and the better the price offered, the more likely consumers are to make purchases at the Barokah Sekopek Fishing in Semarang City. Keywords: Purchase Decision, Price Perception, Store Atmosphere, Word of Mouth